HUBUNGAN KECEMASAN DENGAN CANCER-RELATED FATIGUE (CRF) PADA PASIEN KANKER PAYUDARA PASCA KEMOTERAPI - Novitasari, Devi; Kamayani, Made Oka Ari; Nurhesti, Putu Oka Yuli; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024DO - 10.24843/coping.2024.v12.i03.p07, 2024)
Breast cancer is one of the most prevalent cancers among women. Chemotherapy is a common treatment for breast cancer, but it can cause side effects such as hair loss, nausea, vomiting, and cancer-related fatigue (CRF). Factors contributing to CRF include the cancer itself, the treatments undertaken, and emotional feelings such as anxiety. This study aims to determine the correlation between anxiety and CRF in post-chemotherapy breast cancer patients. This quantitative research used a cross-sectional method conducted from April to May 2024. The sampling technique was purposive sampling (n=30). Data were collected using demographic questionnaires, the Multidimensional Fatigue Inventory (MFI-20), and the State Anxiety Inventory (SAI). The statistical analysis shows that the majority of respondents are in middle adulthood (40-60 years) (73.3%), have high school education (43.3%), are at stage II (70%), and are married (83.3%). The results show that the average anxiety experienced by respondents is 36.47±11.06, indicating mild anxiety. The average CRF experienced by respondents is 55±9.91, indicating moderate CRF. Spearman rank test results show a significant correlation between anxiety and CRF in breast cancer patients, with p = 0.006 and r = 0.488, indicating a moderate positive correlation, meaning that the higher the anxiety, the higher the CRF. The conclusion of this study is that there is a correlation between anxiety and CRF in post-chemotherapy breast cancer patients. Breast cancer patients are encouraged to manage their anxiety symptoms effectively.